A Systematic Theory of Argumentation : the pragma-dialectical approach. - Eemeren, Frans H. van (Cambridge University Press, 2003)
In this book two of the leading figures in argumentation theory present a view of argumentation as a means of resolving differences of opinion by testing the acceptability of the disputed positions. This is a major contribution to the study of argumentation.